Preliminary Screening of Antimicrobial and Phytochemical Studies of Jatropha gossypifolia Linn. - and A. R. Birari2, D. A. Dhale1*, (Recent Research in Science and Technology, 2010)
Abstract The antimicrobial effect of Jatropha gossypifolia Linn. (Euphorbiaceae) leaf extract was evaluated on microbial strains like gram-positive species staphylococcus spp., and Bacillus spp. and gram-negative species Echerichia Spp. and Pseudomonas spp. The solvent used for extraction of plant were Petroleum ether, Alcohol, Chloroform. The alcoholic extract of leaves of Jatropha gossypifolia shows maximum antimicrobial activity. The in vitro antimicrobial valuation was carried out by agar disc diffusion method. The significant antibacterial activity of active extract was compared with standard antibiotic Amphicillin. Â The samples of leaves were further used for the phytochemical studies. Results of the Phytochemical analysis indicated the presence of phenolic compounds, tannins, lignin, starch grains and saponins. Physico-chemical evaluation includes ash values, extractive values and moisture content while Phytochemical isolations includes saponins, tannins, phenols, cellulose, nitrogen, crude proteins and minerals like calcium, phosphorous and potassium. The antibacterial activities of the leaves were due to the presence of various secondary metabolites. Keywords: Antimicrobial, Physico-chemical, Phytochemical, Jatropha gossypifolia